HOW DOES CRYOGENIC FREEZING AFFECT THE CALORIMETRIC PROPERTIES OF LIQUID EGG PRODUCTS? - Ilona Hidas, Karina; Nyulas-Zeke, Ildikó Csilla; Friedrich, László; Visy, Anna; Csonka, Judit; Németh, Csaba (Journal of Engineering & Processing Management, 2019)
Eggs are widely utilized because of their high nutrient value, coagulating, foaming, emulsifying and sometimes even colouring or flavouring facilities in food manufacturing. Production of processed egg products shows an increasing trend. Frozen products belong to first processing, their shelf life can increase up to 1 year. By freezing, a large reduction in microbial loss can be achieved. But different undesirable processes can occur. The effect of freezing on animal cells is highly dependent on freezing parameters. It has a different effect on egg subtituents. Egg yolk undergoes a gelation process while proteins can denaturate. In our study pasteurized liquid egg products (liquid egg white, liquid egg yolk and liquid whole egg) were frozen by dripping into liquid nitrogen. After that, a 14-day frozen storage experiment was carried out at -18°C. Before freezing and on the 1th, 7th and 14th days of storage experiment pH, dry matter content, colour and calorimetric properties (denaturation temperatures and enthalpy of denaturation) with differential scanning calorimetry were tested. For statistical analysis, one-way ANOVA (α = 0.05) was employed. In our experiment, we found no significant change in calorimetric properties of liquid egg white after freezing, but significant decreasing of enthalpy and denaturation temperatures of liquid egg yolk and liquid whole egg was identified. In contrast, frozen storage had a decreasing effect in all these products. Freezing caused a clearly visible colour change in LEW, a visible change in colour of LWE and a very clearly visible change in colour of LEY. In case of LEW and LEY changes increased to clearly visible 14 days. In conclusion, our results show that frozen storage had a greater effect on liquid egg products properties than freezing in liquid nitrogen.